2019
DOI: 10.1111/php.13104
|View full text |Cite
|
Sign up to set email alerts
|

Xanthene Dyes and Green LED for the Inactivation of Foodborne Pathogens in Planktonic and Biofilm States

Abstract: This study evaluated the rose bengal‐ and erythrosine‐mediated photoinactivation against Salmonella Typhimurium and Staphylococcus aureus planktonic and sessile cells using green LED as a light source. The free‐living or 2‐day‐old biofilm cells were treated with different concentrations of the photosensitizing agents and subjected to irradiation. Only 5 min photosensitization with rose bengal at 25 nmol L−1 and 75 μmol L−1 completely eliminated S. aureus and S. Typhimurium planktonic cells, respectively. Eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…When we used KI at 50 mM, a half of the usual KI concentration, in combination with EOS or RB, a strong potentiate effect in the photoinactivation of S. Typhimurium and S. aureus is still observed, compared to the PSs alone [19,20] (Figure 3; p < 0.05). However, it was possible to observe that when EOS at 0.50 µM with KI at 50 mM was used, an additional time of light exposure of 10 min (9.0 J/cm 2 ) are needed, in comparison with the same EOS concentration with KI at 100 mM, to totally photoinactivate S. Typhimurium ( Figure 3A).…”
Section: Photodynamic Inactivation Assaysmentioning
confidence: 96%
See 4 more Smart Citations
“…When we used KI at 50 mM, a half of the usual KI concentration, in combination with EOS or RB, a strong potentiate effect in the photoinactivation of S. Typhimurium and S. aureus is still observed, compared to the PSs alone [19,20] (Figure 3; p < 0.05). However, it was possible to observe that when EOS at 0.50 µM with KI at 50 mM was used, an additional time of light exposure of 10 min (9.0 J/cm 2 ) are needed, in comparison with the same EOS concentration with KI at 100 mM, to totally photoinactivate S. Typhimurium ( Figure 3A).…”
Section: Photodynamic Inactivation Assaysmentioning
confidence: 96%
“…On the other hand, Bonin et al [19] used 5.0 µM of EOS alone to achieve the total inhibition of the bacterium at 5 min of light exposure. While Silva et al [20] reported that it was necessary to use 25 nM RB alone to achieve total inhibition of S. aureus cells with the same time of light exposure (5 min).…”
Section: Photodynamic Inactivation Assaysmentioning
confidence: 99%
See 3 more Smart Citations